The impact of transcranial direct current stimulation on the neuro-muscular control strategies of penalty kicks in soccer players - Wang, H.; Zhang, H.; Li, X.; Zhu, J. (Frontiers in Sports and Active Living, 2025)
Objective: This study aims to investigate the effects of transcranial direct current stimulation (tDCS) on the neuromuscular control of penalty kicks in soccer players. It also analyzes the relationship between neuromuscular control and the stability of motor performance following the intervention.